2021
DOI: 10.1111/and.14327
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin and flunixin meglumine mitigate overloaded copper‐induced testicular and spermatological damages via modulation of oxidative stress and apoptosis in rats

Abstract: This study aimed to evaluate the possible protective actions of chrysin and flunixine meglumine on testicular and spermatological injuries experimentally stimulated by copper. We separated 36 male Sprague–Dawley rats into six equal groups: control, chrysin, flunixine meglumine, copper, copper +chrysin and copper +flunixine meglumine. Chrysin (50 mg/kg/bw/po), flunixine meglumine (2.2 mg/kg/bw/ip) and copper (500 mg/kg/bw/po) were administered day to day for 21 days. Copper administration caused significant mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Therefore, it can be applied prophylactically for the testosterone level that decreases with aging. 33,34 In a study on experimental animals, it was reported that it protected the testicular antioxidant capacity and increased semen quality in rats. 31 Studies evaluating the effects of chrysin on male infertility are summarized in Table 2.…”
Section: Resveratrolmentioning
confidence: 99%
“…Therefore, it can be applied prophylactically for the testosterone level that decreases with aging. 33,34 In a study on experimental animals, it was reported that it protected the testicular antioxidant capacity and increased semen quality in rats. 31 Studies evaluating the effects of chrysin on male infertility are summarized in Table 2.…”
Section: Resveratrolmentioning
confidence: 99%